2017
DOI: 10.1127/fal/2016/0933
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the utility of a frequently used diatom index (IPS) and the diatom ecological guilds in the ecological status assessment of large rivers

Abstract: The Indice de Polluo-Sensibilité Spécifique (IPS) is one of the most frequently used diatom index. Beside this, according to some studies in streams and small rivers the diatom ecological guilds might be effective tools for ecological quality assessment in the future, but the usability of them is not always clear. Our main goal was to compare the robustness of the IPS index and diatom ecological guilds in a large river. For this i) a temporary study was carried out to investigate if there were some differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…However, other, well-known functional traits (planktic life form, high and low profile ecological guilds) may indicate lower conductivity values, similarly to S4 size. Trábert et al (2017) showed already that the relative abundance of diatom taxa under the high profile and motile guilds correlated with each other negatively in lotic systems. The abundance of diatoms belonging to the high profile guild is not directly related to the nutrient level, rather to other habitat factors (Soininen et al 2016) like high light intensity (Trábert et al, 2017).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…However, other, well-known functional traits (planktic life form, high and low profile ecological guilds) may indicate lower conductivity values, similarly to S4 size. Trábert et al (2017) showed already that the relative abundance of diatom taxa under the high profile and motile guilds correlated with each other negatively in lotic systems. The abundance of diatoms belonging to the high profile guild is not directly related to the nutrient level, rather to other habitat factors (Soininen et al 2016) like high light intensity (Trábert et al, 2017).…”
mentioning
confidence: 89%
“…Trábert et al (2017) showed already that the relative abundance of diatom taxa under the high profile and motile guilds correlated with each other negatively in lotic systems. The abundance of diatoms belonging to the high profile guild is not directly related to the nutrient level, rather to other habitat factors (Soininen et al 2016) like high light intensity (Trábert et al, 2017). The dominance of low profile diatom taxa is characteristic in temporary and permanent water courses with frequent disturbance events and low nutrient content (Novais et al, 2014).…”
mentioning
confidence: 89%
“…Beside abiotic factors, biotic factors (e.g., interspecific competition) also affect the relative abundance of these traits. Regarding traits related to the attachment mechanism and lifeform of diatoms, the proportion of high-profile groups in running waters is typically low because they have a long stalk that attach to the substrate and is easily torn off by flowing water [51,52]. During periods of low water discharge, their proportion was slightly higher in the epiphyton, partly because they are adapted to low current velocities [53].…”
Section: Traits Of Diatom Assemblagesmentioning
confidence: 99%
“…Therefore, the amount of this group is typically the largest in flowing aquatic habitats. This group is also the dominant ecological group in the epiphyton of the main arm of the Danube [52]. In addition, LPGs are more common in shaded environments [54] and are able to withstand washing out and physical damage, explaining their domination of unstable habitats [27,53].…”
Section: Traits Of Diatom Assemblagesmentioning
confidence: 99%
See 1 more Smart Citation